Nutritional assessment of patients undergoing hematopoietic stem cell transplantation: approach using GLIM criteria and clinical outcomes - dos Santos Ribeiro, Francisca Rosana (2025)
Objective: to apply the Global Leadership Initiative on Malnutrition (GLIM) criteria in patients undergoing HSCT and verify their association with clinical outcome and length of hospital stay. Method: a cross-sectional study was conducted with 278 HSCT candidates from a tertiary university hospital in Fortaleza - Ceará. Demographic, clinical, dietary, and anthropometric data were collected through medical record analysis between 2019 and 2022. The prevalence of malnutrition was determined using the GLIM criteria. Results: the majority of the sample was female (51.4%, n=143). Of these, the most prevalent treatment was autologous HSCT (63%, n=174). According to the results obtained using the GLIM criteria, 21% (n=36) and 32% (n=33) were diagnosed with malnutrition in the autologous and allogeneic HSCT groups, respectively. Conclusion: the present study demonstrated that malnutrition, according to the GLIM criteria, is not associated with longer hospital stays or clinical outcomes in patients undergoing HSCT. However, it shows a high prevalence of malnutrition by the GLIM method, highlighting the need for early diagnosis to reduce the percentage of patients arriving malnourished for transplantation.